Bullying victimization and suicide attempts among adolescents in 41 low- and middle-income countries: Roles of sleep deprivation and body mass - Wenxin Bao; Wenxin Bao; Yi Qian; Yi Qian; Wenjing Fei; Shun Tian; Yiran Geng; Shaishai Wang; Shaishai Wang; Chen-Wei Pan; Chun-Hua Zhao; Tianyang Zhang (Frontiers in Public Health, 2023)
BackgroundSuicide is the fourth leading cause of death for adolescents, and globally, over 75% of completed suicides occur in low- and middle-income countries (LMICs). Bullying has been proven to be closely related to suicide attempts. However, further understanding of the mechanisms underlying the relationship between bullying and adolescents' suicide attempts is urgently needed.MethodsWe used data from the Global School-based Student Health Survey (GSHS) (2010–2017) from 41 LMICs or regions. This study was based on questions assessing bullying victimization, suicide attempts, sleep deprivation, and body mass. Chi-square tests were used to explore the correlations among the main variables. The mediating role of sleep deprivation and the moderating role of body mass index (BMI) were analyzed using PROCESS.ResultsThe results showed a positive association between bullying victimization and suicide attempts. Sleep deprivation partially mediated the relationship between the frequency of being bullied and suicide attempts. In addition, sleep deprivation played a full or partial mediating role in the relationship between different types of bullying and suicide attempts. BMI moderated the relationships between the frequency of being bullied and suicide attempts, between being made fun of about one's body and sleep deprivation, and between sleep deprivation and suicide attempts.ConclusionBeing bullied has a positive effect on suicide attempts, which is mediated by sleep deprivation and moderated by body mass. The results of this study are consistent with the stress-diathesis model of suicide, suggesting that being bullied is one of the stressors of suicide in adolescents, while sleep deprivation and body mass are susceptibility diatheses of suicide. The results are conducive to identifying adolescents at a high risk of suicide, suggesting that there is a need to pay more attention to bullied adolescents, especially their sleep quality and body mass, and design effective intervention measures to improve the current situation of adolescent suicide in LMICs.